Hybrid Justice in Vanuatu : The Island Courts - Goddard, Michael; Otto, Leisande (World Bank, Washington, DC, 2014)
Island courts have been in operation in Vanuatu since 1984. Official documents have hitherto provided little information on their practical operations or utility, and our preliminary research in 2010 found that not much was known at the state governance level about their real circumstances. In 2011, we conducted fieldwork research on five islands, Efate, Santo, Malekula, Epi, and Tanna, to provide better information on the practical operations of island courts and their use by ni-Vanuatu. The author found that although island courts have the potential to provide a valuable service to rural ni-Vanuatu, a number of problems must first be addressed. Their resources and support networks need to be improved and a regularity in these services guaranteed. Networking with other governance institutions (including nongovernmental organizations [NGOs]) at the local level in the provinces could be facilitated, as cooperation among these institutions would be beneficial to all of them. It will also be useful to nencourage the island courts to strengthen the flexibility and creativity that they are, of necessity, already developing, particularly in relation to matters of 'kastom.'